Three-Dimensional Channel Potential Model of a Triple Gate MOSFET based on Conformal Mapping Technique. Issue 3 (4th May 2022) - Bose, Ria; Roy, J. N.
Abstract : In this paper, an analytical channel potential model of an experimental nano-scaled triple gate MOSFET has been developed that is valid in the subthreshold regime. The potential model is derived by applying the Schwarz–Christoffel transformation method and conformal mapping techniques. The model is derived by superposing the influence of top gate on the potential barrier with the 2D potential solution, which is obtained by considering the presence of only two side gates. From that, the threshold voltage model of the device is also evaluated. To validate our model, the result has been compared with numerical simulation data from 3D TCAD Sentaurus that shows good accuracy for channel length (as short as 30 nm) considered for our device.